The illness feeling in the preoperative of cardiac surgery - a phenomenological study - Rosa Helena Silva Souza; Maria de Fátima Mantovani; Liliana Maria Labronici (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2006)
This is a qualitative research with a phenomenological approach research had as an objective to learn the feelings and perceptions of the illness which is in preoperative cardiac surgery. This work, performed in the Hospital de Clinicas of the Parana Federal University, with 11 persons in preoperative for cardiac surgery, during March and April of 2004. The speeches analyses resulting two thematic units: Scared bodies - A reality to be transcendental and The hope to be a newly body. The first encloses the scared that touches who lives in a preoperative period. The second category related to the possibility of gain a better life through the new body conquered with the surgery. It was possible to revealed this studied phenomena and discover the necessity of an interaction between the nurse and the sick body in the per-operative situation, looking for his wellness. Key words: Cardiac Surgery; Nursing; Preoperative Cares.